2017
DOI: 10.4172/2153-2435.1000568
|View full text |Cite
|
Sign up to set email alerts
|

Gas Chromatography-Mass Spectrometry (GC-MS) Analysis of Aqueous Extract of Daniellia oliveri Stem Bark

Abstract: A novel Gas Chromatography-Mass Spectrometry (GCMS) analysis of aqueous extract of Daniellia oliveri stem bark was performed to identify the composition and percentage abundance of the various phytochemical constituents of Daniellia oliveri stem bark. The extract was obtained using 1:4 (w/v) of the pulverized stem bark in distilled water. Gas Chromatography-Mass Spectrometry Analysis was carried out on a Perkin Elmer Turbo Mass Spectrophotometer while measurement of peak areas and data processing were carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 3 publications
1
10
0
1
Order By: Relevance
“…The variation in the abundance is in agreement with [1] that, different extracts possesses unique physicochemical characteristics which may be due to the molecular weight of the chemical entities as the compounds are naturally present in significant quantities. This is also in agreement with the work of [33], who identified D. oliveri from its ethnobotanical and industrial importance. In this study, the GC-MS analysis of methanolic leaf extract revealed the presence of Benzo[h]quinoline, 2,4-dimethyl-, similar to the work of [34] that, fused quinoline derivatives produce antimalarial effects.…”
Section: Discussionsupporting
confidence: 92%
“…The variation in the abundance is in agreement with [1] that, different extracts possesses unique physicochemical characteristics which may be due to the molecular weight of the chemical entities as the compounds are naturally present in significant quantities. This is also in agreement with the work of [33], who identified D. oliveri from its ethnobotanical and industrial importance. In this study, the GC-MS analysis of methanolic leaf extract revealed the presence of Benzo[h]quinoline, 2,4-dimethyl-, similar to the work of [34] that, fused quinoline derivatives produce antimalarial effects.…”
Section: Discussionsupporting
confidence: 92%
“…n-Hexadecanoic acid acts as antioxidant and anti-inflammatory [35]. cis-Vaccenic acid act as anti-asthmatic, antiinflammatory and lowers total cholesterol and triglycerides levels [28,36]. Octadecanoic acid is used hypercholesterolemic, antiarthiritic, antiinflammatory, hepatoprotective, nematicide and antimicrobial [28].…”
Section: Gc-ms Analysis Of T Indica Leaves Aqueous Extractmentioning
confidence: 99%
“…Hexadecanoic acid (palmitic acid) is a fatty acid and it has been suggested as an active antimicrobial and antidiarrhoeal agent [70]. It was also documented by Yakubu et al [71] that Hexadecanoic acid is an anti-inflammatory agent and antioxidant. It has been suggested that 9,12-Octadecadienoic acid and oleic acid prevent the development of adreno-leuko dystrophy (ALD), a disease that damages the brain and the adrenal glands.…”
Section: Discussionmentioning
confidence: 99%